Integrating Content and Language Instruction in Multilingual Education: Insights from a CLIL-Based Teacher Training Program - Gulshair Mamatova; Nurgul Osmonova (Asia Pacific Journal of Management and Education (APJME), 2025)
This article substantiates the relevance of multilingual education in alignment with Kyrgyzstan’s national development strategies, which emphasize preparing citizens proficient in multiple languages. The study examines the potential of the Content and Language Integrated Learning (CLIL) methodology as an effective approach to achieving these national objectives. The main purpose of this research is to explore the theoretical foundations and practical benefits of CLIL in a multilingual educational environment and to develop recommendations for training future teachers. An action research design was implemented in three cycles, each comprising planning, action, observation, and reflection stages. The participants were students from Jalal-Abad State University, and their language development was monitored throughout the study. The findings demonstrated a notable improvement in Russian language proficiency following the implementation of CLIL and extracurricular language activities: the proportion of students achieving level B1 increased by 14%, and level A1 by 19%. The third measurement confirmed that 38.4% of students reached level A2 and 50% level A1. Overall, the CLIL methodology proved to be a promising and practical tool for improving linguistic, cognitive, and professional competencies, supporting the preparation of competitive specialists for multilingual and international educational contexts.